The Influence of TikTok Educational Content About Malocclusion on The Knowledge of Adolescents in Purwokerto - Sinta Nurrohmah; Wisnu Widjanarko; Dian Noviyanti Agus Imam (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Malocclusion is the third most prevalent dental and oral health problem worldwide. The global prevalence of malocclusion among adolescents is approximately 56%. Malocclusion can be treated through orthodontic treatment. Adolescents' interest in undergoing orthodontic treatment can be influenced by their knowledge about malocclusion. TikTok is one of the social media platforms that can be used to disseminate information in order to increase adolescents’ knowledge. Methods: This research is a quasi-experimental study using a pretest-posttest control group design. Sampling was conducted using proportional sampling and simple random sampling to determine the school locations involved in the study. The number of respondents from each school was then determined using stratified random sampling. A total of 241 respondents from five high schools in Purwokerto participated in this study. Data were collected using a questionnaire and analyzed using the Wilcoxon Signed Rank Test for pre-test and post-test comparisons within groups, and the Kruskal-Wallis test for comparisons between the intervention and control groups. Results: The results showed a significant difference between pre-test and post-test scores in the intervention group exposed to the educational content on TikTok. There was also a significant difference in the increase in knowledge between the intervention group and the control group (p < 0.05). Conclusion: The conclusion of this research is that educational content about malocclusion delivered through TikTok has a significant effect on increasing the knowledge of malocclusion among adolescents in Purwokerto.